Improving the Quality of Service Using the IPA and PGCV Methods at BPJS Kesehatan, South Tangerang - Rini Alfatiyah; Sofian Bastuti (Jurnal Ilmiah Teknik Industri, 2023)
BPJS Health is tasked with administering the health insurance program, or better known as the National Health Insurance (JKN). The problem that occurs is that there are still many community reports indicating that BPJS Health services in Tangerang are still not good. The goal to be achieved by the author is to find out the quality of service that will be provided by the South Tangerang City BPJS Health Service Office to users and provide suggestions for improvement to increase customer satisfaction at the South Tangerang City BPJS Health Service Office. The method used in this paper uses Importance Performance Analysis (IPA) and Potential Gain in Customer Service (PGCV). The results of this study are IPA analysis stating that the majority of services are in quadrant IV, which means that the service is satisfactory but services that are not considered important by customers. While 6 services are considered important by customers but are not satisfactory. Meanwhile, the PGCV analysis stated that long queue waiting times were a top priority for improvement.